Physical activity and supplementation as alternative methods in migraine prophylaxis -literature review - Daria Aleksandrowicz; Marta Głąbień; Paweł Miłkowski; Anna Kuśnierz; Zofia Jakubczak; Aneta Kondratowicz; Patryk Śliwiak; Karolina Kusiak; Maria Weronika Zimniak; Olga Wieczorek (Nicolaus Copernicus University in Toruń, 2024)
Migraine is a common and debilitating neurological disorder. It is crucial to realize that migraines are distinguished from other types of headaches. People suffering from migraine are often unable to function normally, neglecting work and daily duties. The associated costs burden not only the patients but also their family and social life. What is more, many psychiatric comorbidities are common in migraine patients. Because of all these factors, preventive treatment is essential because it can decrease migraine frequency and improve quality of life. There are many preventative medications but satisfactory improvement in reducing the frequency of migraine attacks may not be achieved without modification of lifestyle including taking care of physical activity and supplementation. Many studies have shown that moderate physical activity and supplementation of vitamins B2, D, coenzyme Q10 and magnesium has a positive effect on reducing duration and frequency of the migraine attack.